Registered Nurses' Experience of Person‐Centred Care Through Digital Aids in Primary Care Setting During the COVID‐19 Pandemic - Annika Kjällman Alm; Ove Hellzen; Malin Rising‐Holmström (Nursing Open)
ABSTRACT Aim The aim of this study was to describe registered nurses' experience of person‐centred care through digital media during the COVID‐19 pandemic. The first wave of COVID‐19 took healthcare services worldwide by surprise and affected all levels of care. Registered nurses within primary care settings had to adjust to new meeting forums with patients and in collaborations with other organisations to transfer patients from hospital to home care in a safe and secure manner using digital aids. Design Interviews with 17 registered nurses within primary care settings were conducted. Interviews were transcribed verbatim and analysed using qualitative content analysis. Methods Qualitative using semi‐structured interviews. Results Digitalisation requires organisational changes, with four subcategories. The second category, digitalisation, facilitates person‐centred care, with two subcategories. Main findings showed digitalisation as a possibility to enhance person‐centred care to benefit the individual. The patients would have the possibility of obtaining professional care in their own home, enhancing the continuation of care. Digitalisation of primary care tasks demanded organisational changes of different kinds. This meant implementing innovative digital tools or artificial intelligence and developing a mental frame of mind that embraces new ways and activities to perform primary care through technology. Public Contribution Registered nurses saw enhancement of person‐centred care through digital media as something positive. However, they also voiced concerns that some patients, such as self‐damaging teenagers, new patients and multi‐sick patients, would be unsuitable for digital meetings. They also emphasised that the digitalisation of person‐centred care requires organisational changes. The study addressed the problems faced by the rapid conversion from traditional face‐to‐face care to digital care in the beginning of the COVID‐19 pandemic within a primary care setting. There is a need for continued education on best communication practices with a primary focus on person‐centred care. Since communication is key in the continuation of care, this needs to be addressed by both health centre management and educators.